2021
DOI: 10.1021/acs.jpclett.0c03737
|View full text |Cite
|
Sign up to set email alerts
|

Design of Novel Highly Efficient Yellow-Orange Color-Tunable Luminescence in Rb2Sr1–yCayP2O7:xEu2+ Solid Solutions for White Light-Emitting Diodes

Abstract: Traditional white light-emitting diodes (WLEDs) are limited by the energy loss due to reabsorption. Integrating binary complementary color phosphors with near-ultraviolet (n-UV) LED chips can be a good solution, and the core of it is to develop yellow-emitting phosphors. In this work, we have designed Rb 2 Sr 1−y Ca y P 2 O 7 :xEu 2+ solid solutions with yelloworange color-tunable luminescence. The crystal structure, luminescence properties, and potential applications for WLEDs were explored systematically. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…14). It is worth noting that as reported earlier by Zhang et al 22 refinement was conducted using the structure of Rb 2 SrP 2 O 7 (space group C2/c, no. 15) as a model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14). It is worth noting that as reported earlier by Zhang et al 22 refinement was conducted using the structure of Rb 2 SrP 2 O 7 (space group C2/c, no. 15) as a model.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Rb 2 CaP 2 O 7 :Eu 2+ , Hong et al reported that at 140 °C this reddish-orange-emitting phosphor retained only ∼30% of the initial integrated intensity (∼30%@140 °C). 19 22 Nevertheless, the thermal quenching issue has not been studied in their work and is unknown. Thus, boosting the luminescence thermal stability of phosphors is vital to enabling their potential applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphor-converted white light-emitting diode (pc-wLED) lighting has acquired incredible accomplishment since the successful invention of the InGaN blue LED by Isamu Akasaki et al, awarded the Nobel Physics Prize in 2014 . Presently, pc-wLEDs have become an increasingly hot topic due to a wealth of unique advantages, such as environmental friendliness, long lifetime, and tunable colors allowing for a wide utilization in the fields of bioimaging, anticounterfeiting, lighting, medical applications, and many more. Exploring classical phosphors, being the essential ingredient of solid-state lighting emitting diodes (SS-LEDs), has been performed by introducing rare earth (RE) ions into inorganic host materials. In the early 1990s, the phosphors of alkali-earth metal sulfides (MgS, CaS, SrS, and BaS) doped with Eu 2+ , Eu 3+ , and Ce 3+ were extensively studied for cathodoluminescence and electroluminescence displays. , A series of commercial CaS:Eu phosphors have recently been investigated as solid-state light sources due to the red emission near 645 nm. SrS is considered as a potential substrate matrix owing to its small vibrational frequencies and narrow band gap energy. , The luminescence properties of SrS can be modulated over the entire region of the visible electro-magnetic spectrum when doped with appropriate RE ions.…”
Section: Introductionmentioning
confidence: 99%
“…The pc‐WLEDs have outstanding characteristics of energy saving, 5 fast response, 6 high luminous efficiency, 7 stable output, 8 long service time, 9 etc with respect to conventional incandescent lamps. Generally, the previous fabrication technique involving the pc‐WLEDs based on only yellow‐emitting phosphors (Y 3 Al 5 O 12 :Ce 3+ ) onto a blue LED chip would suffer from low color rendering index (CRI) (<75) 10,11 and high correlated color temperature (CCT) (>7000 K) 12 which are not suitable for indoor lighting due to the blue light affects 13 . Fortunately, the combination of blue/green/red‐emitting phosphors covered on the near‐ultraviolet (NUV) and ultraviolet (UV) LED chips is well‐known as a popular approach to fabricate the pc‐WLEDs by avoiding the above disadvantages.…”
Section: Introductionmentioning
confidence: 99%